Intravitreal pegaptanib for the treatment of ischemic diabetic macular edema - Kiire CA (Dove Medical Press, 2015)
Christine A Kiire, Rupal Morjaria, Anna Rudenko, Alexina Fantato, Lewis Smith, Amy Smith, Victor Chong Oxford Eye Hospital, Oxford University Hospitals NHS Foundation Trust, Oxford, UK Purpose: Pegaptanib has been shown to be effective in treating diabetic macular edema (DME). In the original Phase II/III trial, however, patients with macular ischemia were excluded. In this study, we treated patients with ischemic DME. Methods: Macular ischemia was defined as a 30% increase in the area of the foveal avascular zone (FAZ) at 45 seconds on fundus fluorescein angiography. In addition, the participants had diffuse foveal-involving DME with a central subfield thickness (CST) of >300 µm on spectral-domain optical coherence tomography. Five intravitreal pegaptanib injections were given 6 weeks apart. The final study visit was 6 weeks after the fifth injection. The primary outcome was change in the size of FAZ. Secondary outcomes were change in best-corrected visual acuity (BCVA) and the change in CST. Results: Thirty participants were enrolled. Three were unable to complete the full course of treatment. Their outcomes were carried forward for the first part of this analysis. There was no statistically significant change in the mean size of the FAZ from baseline to the final visit. Subclassifying participants as those with minimal/moderate ischemia (16 participants, FAZ area <1,000 pixels) and those with more severe ischemia (14 participants, FAZ area >1,000 pixels) also showed no statistically significant change in the mean area of the FAZ. On average, BCVA increased and CST decreased from baseline to the final visit, but these changes were not statistically significant. Using per protocol analysis on those participants who completed the full course of treatment, the mean BCVA increased from 49.2 to 53.9 letters (P=0.046). Conclusion: In this study, intravitreal injection of pegaptanib did not significantly alter the size of the FAZ in participants with varying degrees of ischemic DME. There was, however, a significant improvement in mean BCVA in those who completed the treatment course. Keywords: macular ischemia, anti-VEGF, pegaptanib, diabetic macular edema